THE DEVELOPMENT OF MEAT CATTLE BREEDING IN CONDITIONS OF RUSSIAN EMBARGO - V. Svinukhov; S. Senotrusova; I. Makarova (Вестник университета)
Problems of domestic meat production in terms of food embargo relevant for the development of further import substitution. A key factor to ensure a balance of internal market of dairy products is the dynamic development of domestic agricultural production, raw materials and food and the replacement of imported products. The article examines the dynamics of the market of animal products to reflect changes in its geographical pattern, the volume and value of import to the Russian Federation in the conditions of embargo. To address issues of import substitution of agricultural products of the pastoral industries is necessary to study regional problems of sustainable development of rural areas taking into account features of development of the village, including the production characteristics of beef cattle.